PERAN ORANG TUA DALAM PROSES PEMBELAJARAN DARING ANAK USIA SEKOLAH DASAR DI DESA JANGGALAN KUDUS - Isti Zulfa Nida; Moh. Kanzunnudin; Khamdun (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article describes parents’ role and obstacles during online learning process based on parents’ parental education background and career. The study in this article used the case study qualitative approach. The subjects in the study involved parents and elementary school children. The techniques in this study were interviews, observation, documentation, recording, and data transcription. The result indicated that 1) parents’ roles in online learning were parents as a teacher at home, parents as a facilitator, parents as a motivator, and parents provided supervision to children’s learning from home. 2) Parents’ obstacle in guiding the children’s learning during studying at home came from the career parents who must work all day activity outside had limited time in guiding the children studying at home, the parents who have basic education had an obstacle to explain the learning material in detail to their children, parents had an obstacle to have facilities and infrastructure like handphone, and the parents were impatient during guiding the children study at home.